2021
DOI: 10.3389/fmolb.2021.599221
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Binders of Mtb Universal Stress Protein (Rv1636) Through an in silico Approach and Insights Into Compound Selection for Experimental Validation

Abstract: Millions of deaths caused by Mycobacterium tuberculosis (Mtb) are reported worldwide every year. Treatment of tuberculosis (TB) involves the use of multiple antibiotics over a prolonged period. However, the emergence of resistance leading to multidrug-resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB) is the most challenging aspect of TB treatment. Therefore, there is a constant need to search for novel therapeutic strategies that could tackle the growing problem of drug resistance. One such stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Further, using computational docking and library screening approaches, of the two natural compounds that could bind to MSMEG_3811(43), STOCKIN42384 (Figure 7A) had a docking score better than that of cAMP, and engaged Ala40 (a key residue for cAMP binding (10)) and Glu57 in hydrogen bonding. The second compound, STOCKIN74667 (Figure 7A), was hydrogen bonded to Gly114, also important for cAMP binding.…”
Section: Resultsmentioning
confidence: 99%
“…Further, using computational docking and library screening approaches, of the two natural compounds that could bind to MSMEG_3811(43), STOCKIN42384 (Figure 7A) had a docking score better than that of cAMP, and engaged Ala40 (a key residue for cAMP binding (10)) and Glu57 in hydrogen bonding. The second compound, STOCKIN74667 (Figure 7A), was hydrogen bonded to Gly114, also important for cAMP binding.…”
Section: Resultsmentioning
confidence: 99%
“…Our other studies have shown that Rv1636 is a potential virulent protein that overexpresses host-derived stress conditions in response to mycobacterial infection. An in vitro experiment revealed that Rv1636 has a substantial binding affinity for ATP and cAMP [ 53 , 54 ]. As a result, we performed molecular docking of -Amyrin with Rv1636 using these two compounds as a control.…”
Section: Methodsmentioning
confidence: 99%
“…After sorting compounds based on the repetitive entries, 100 compounds were found unique and used for ligand preparation. 30 The structure of most of the compounds was downloaded from PubChem and ZINC databases, and the structures of other compounds were drawn using the chem-sketch Marvin visualization (https://chemaxon.com/products/marvin). All the compounds for this study were selected based on their respective mechanism toward the targeted receptors so that we can predict the best outcome for the particular disease pathway.…”
Section: Library Preparationmentioning
confidence: 99%
“…For the virtual screening process, all the libraries were subjected to the pdbqt format of receptor protein. 30 Furthermore, all the compounds were subjected to pharmacological screening, such as ADME and toxicity, followed by the Lipinski rule of five.…”
Section: Library Preparationmentioning
confidence: 99%